Scents and sensibility - Quinn, Spencer (Quinn, Spencer. Chet and Bernie mystery., 2015)
When his neighbor gets in trouble for cactus smuggling, Bernie Little, along with his dog, investigates and discovers dangerous goings-on in the desert that seem to be linked to a strange festival, a cult, and a long-ago kidnapping.